The Impact of Diabetes Mellitus on Patients’ Quality of Life - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study aimed to measure the impact of diabetes mellitus (DM) on patients’ quality of life (QoL). Materials and Methods: This cross-sectional study involved DM patients that underwent follow-up at a hospital in central Malaysia. Data were collected using self-developed and self-administered questionnaire. Statistical analysis was performed using Statistical Package for the Social Sciences version 24. Results: Around 75 (56.8%) of the patients were satisfied with their daily routine life activities. A total of 88 (66.7%) were also satisfied with their family and friends’ relationships. On the contrary, 109 (82.6%) were not satisfied with their sexual life. There was a statistically significant correlation observed between age and QoL. Conclusion: This study showed that the majority of DM patients had moderate QoL. Diet, living conditions, and concerns about the future had also a greater influence on their overall QoL.